Bilateral radicular cyst mimicking dentigerous cyst: a case report - Khamila Gayatri Anjani; Annisa Putri; Lusi Epsilawati (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2022)
Objectives: The aim of this case report is to describe radiographically the specific features of periapical cysts to differentiate them from dentigerous cyst lesions despite their similar clinical appearance. Case Report: A 21-year-old female patient came to Dental Hospital in Bandung with a referral for a cone-beam computed tomography (CBCT) examination with a clinical diagnosis of suspected right mandibular dentigerous cyst and left mandibular periapical cyst. The patient said that during the past month, swelling had appeared on both sides of the jaw, which was getting bigger, the pain was intermittent, and it was disturbing when eating. Intraoral examination showed gingival enlargement, muccobucal fold disappeared. Extraoral examination, facial asymmetry was found due to unilateral swelling. Radiographic examinations showed both lesions were oval, unilocular, radiolucent internal structures with an average density of 4.7-32 HU resembling soft tissue density, corticated or radiopaque borders, caused expansion of the mandibular corpus buccally and lingually and to mesial and distal, cortical thinning and displacement of the inferior mandibular canal. Conclusion: Lesions on the jaws have almost the same clinical appearance, but through CBCT examination the type of lesion can be well determined. Periapical cyst lesion with large size has a clinical appearance like dentigerous lesions, but radiographically will show a different specific picture.